A descriptive study of health behaviors and attitude towards change among children with disabilities - Morgan, Kristen; Graves, Myia; Reck, Hannah (Journal of Health and Physical Literacy, 2024)
Purpose: The purpose of this study was to describe health behaviors such as physical activity (PA), healthy eating, and body composition along with perceptions of eating healthy and attitude towards change among children with disabilities following a Camp for Health & Motor skill Promotion (CHAMP). Methods: Sixteen children with autism and other disabilities (n = 16), aged 5 to 12 years, participated in the current study. Children completed a healthy behaviors survey at the beginning of CHAMP with the help of a councilor. After CHAMP, children completed an attitude towards change survey. Body Mass Index (BMI) was calculated with height and weight measurements. Descriptive data were analyzed through case-wise comparisons and describing the children who participated in the study. Results: 11 children had more unhealthy eating behaviors compared to healthy eating behaviors and 4 children ate more healthy foods. None of the children engaged in the recommended level of PA (everyday) and half were considered overweight/obese. Most of the children learned about health behaviors and indicated a desire to change their habits. Conclusion: The study data supports the need for an increase in PA opportunities and healthy eating behaviors among children with disabilities.